2020
DOI: 10.1108/wje-07-2020-0250
|View full text |Cite
|
Sign up to set email alerts
|

Application of fuzzy MOORA method in the design and fabrication of an automated hammering machine

Abstract: Purpose In most developing countries riveting, upset forging and punching operations among others are performed using manual hammering technique. The use of the manual method increases production time and reduces efficiency. The use of the manual approach is predominantly due to the high cost of imported automated hammering machines (AHM) which the majority of the end-users are incapable of acquiring. The purpose of this paper, therefore, is to produce an AHM that is affordable using an effective material sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Based on the review of the various assessment approaches for supply chain [13,14,16,59], fuzzy logic approach was highly preferred by researchers owing to its capability to incorporate and deal with problems involving impreciseness and vagueness phenomena. From literature, it is evident that researches adopted fuzzy multi-criteria decision-making methods in numerous sectors; for example: to assess sustainability of small urban neighbourhoods [60] and resilience of urban communities [61]; to locate supply chain logistic centres [62]; analysing safety hazards and occupational risks [63]; ranking alternative construction project plans [64] and renewable energy parks [65]; selection of material in the design and fabrication process [66]. The disadvantages of other approaches as that they are inflexible and must be restructured to appropriate the prevailing new circumstances as they involve several levels of linguistic terms or different membership functions usage.…”
Section: Models Focused Onmentioning
confidence: 99%
“…Based on the review of the various assessment approaches for supply chain [13,14,16,59], fuzzy logic approach was highly preferred by researchers owing to its capability to incorporate and deal with problems involving impreciseness and vagueness phenomena. From literature, it is evident that researches adopted fuzzy multi-criteria decision-making methods in numerous sectors; for example: to assess sustainability of small urban neighbourhoods [60] and resilience of urban communities [61]; to locate supply chain logistic centres [62]; analysing safety hazards and occupational risks [63]; ranking alternative construction project plans [64] and renewable energy parks [65]; selection of material in the design and fabrication process [66]. The disadvantages of other approaches as that they are inflexible and must be restructured to appropriate the prevailing new circumstances as they involve several levels of linguistic terms or different membership functions usage.…”
Section: Models Focused Onmentioning
confidence: 99%
“…In the hybrid fuzzy-MOORA technique, the options of decision makers are conveyed in relation to linguistic variables set [4,9].…”
Section: Methodsmentioning
confidence: 99%
“…They reported that the design and fabrication process is one of the key factors that shape the decision making criteria for maintaining a sustainable supply chain. Emovon et al backed this conclusion [18]. Al-Zabidi et al [17] pointed out that digitalization in product design is one of the sustainable attributes that enable the realization of a sustainable supply chain.…”
Section: Sustainability and Product Development Process: A Brief Reviewmentioning
confidence: 99%